Pengaruh Service Quality, Company Image dan Product Quality terhadap Customer Loyalty yang Dimediasi Customer Satisfaction Pada Pelanggan Indihome - Aslam, Zaura Muthia; Engriani, Yunita (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to determine the effect of Service Quality, Company Image and Product Quality on Customer Loyalty Mediated by Customer Satisfaction on Indihome Customers in Padang City using the Structural Equation Modeling (SEM) method. This research is an explanatory study that uses quantitative data with the sample selection technique used, namely purposive sampling. The sample in this study were 90 respondents who were Indihome customers in Padang City. Data collection using questionnaires distributed to Indihome customers. The results showed a positive and significant influence between Service Quality, Company Image and Product Quality on Customer Satisfaction. In addition, Customer Satisfaction also has a positive and significant effect on Customer Loyalty. Furthermore, Customer Satisfaction is proven to significantly mediate the relationship between Service Quality, Company Image, and Product Quality on Customer Loyalty. The implications of these findings can be a reference for Indihome in improving service strategies, strengthening company image, and improving product quality to maintain and increase customer loyalty.